Format Pendidikan Islam Di Era Globalisasi - Mujibur Rahman (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2017)
The concept of education that needs to be updated is to change the view of the dichotomy of science in Islam by harmonizing the verses of illahiyah with kauniyah verse, God - human relationship in the form of education - antropo theo - centric, harmonize faith with science, as well as harmonize the fulfillment of spiritual and physical needs.